TIP – Training of Intensive medical support in the case of a Pandemic - Lütcke, Björn; Günther, J.; Köhnen, Julia; Puchinger, A.; Schmidt, Anita (GMS Journal for Medical Education, 2021)
The COVID-19 pandemic has led to a short-term sharp increase in the demand for auxiliary staff in emergency rooms and intensive care units. Against this background student tutors of the Medical Faculty Erlangen have developed a training concept. The aim was to familiarize students in the clinical section quickly and effectively with skills that are particularly important in a clinical assignment as (student) assistant in the care of corona patients (e.g.: personal protective equipment, intubation assistance, arterial blood collection, assessment of blood gas values and ventilation parameters). In a blended learning concept, learning materials were prepared in ad-vance and then implemented and deepened in a presence phase. The selection of learning materials and the low supervision ratio (1:2) made it possible to realize an internally differentiated approach. The offer met with great interest among students of all clinical semesters and was evaluated very positively. The skills learned can be applied widely even independently of a pandemic.
CRIS-Team Scopus Importer:2021-03-05
Keywords: COVID-19; Internal differentiation; Peer-teaching; Self-protection